Gerry Saputra Implementasi Radio Frequency Identification Dan Camera Pada Sistem Gerbang Masuk Dan Keluar Perbatasan Negara Berbasis Arduino Uno Dan Gui - Gerry Saputra; Ruri Hartika Zain; Riska Robianto (Journal of Computer Scine and Information Technology, 2023)
Currently, the activities of entering and leaving the country in Indonesia require a long period of time and incur significant costs in day-to-day operations. One of the reasons is the increasing population who wishes to travel in and out of the country, leading to long queues and consuming much time. Moreover, the process of identifying passport legality is still done manually, resulting in a time-consuming passport handling process. The purpose of this research is to develop a system that facilitates traveling in and out of the country and registers passport data for those who do not have an ID Tag, thereby reducing the duration of travel in and out of the country.